(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article examines the impact of the national project "Education" on the development of the educational sphere of the Russian Federation, evaluates its effectiveness at the stage of completion of the first cycle of implementation of national projects. Started in 2019, this stage is coming to its end in 2024. The authors note the significant progress made by the country within the international educational space, the improvement of Russia’s position in the ratings and assessments of the quality of education. The article concludes that, thanks to the implementation of the national project "Education", the Russian Federation was able to increase its rating in the group of international studies and outperform other developed countries. The authors also focus on the problem of the development of the field of additional education, the involvement of children, and the increase in the number of organizations providing additional education services in the country. Based on the results of the analysis of the key indicators of the national project "Education", the authors conclude that the national project "Education" is an effective tool for achieving the strategic goals of the Russian state in the educational sphere.